INNOVATIONS IN EDUCATIONAL SYSTEM IN THE CONDITIONS OF INDEPENDENCE OF KAZAKHSTAN - Сайфутдинова, Т.Р. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2021)
This Article examines the analysis of the development of the secondary education system of the Republic of Kazakhstan during the period of gaining state sovereignty. The periods of innovative development of the secondary education system in the Republic of Kazakhstan are highlighted and substantiated, the dynamics of development of innovative educational institutions is characterized.
Keywords: innovation; innovation processes; system of education; specialization; educational standards